4-chloro-orto-cresol activates ryanodine receptor more selectively and potently than 4-chloro-meta-cresol. (June 2020) - Skaliczki, Mariann; Lukács, Balázs; Magyar, Zsuzsanna É; Kovács, Tünde; Bárdi, Miklós; Novák, Szabolcs; Diszházi, Gyula; Sárközi, Sándor; Márton, Ildikó; Péli-Szabó, Judit; Jóna, István; Nánási, Péter; et al.
Graphical abstract: Highlights: Chlorocresol stereoisomers 4CMC, 4COC and -3CPC were tested in Ca 2+ release and ATP-ase activity assays using SR vesicles All isomers cause Ca 2+ release by activation of RyR and inhibit SERCA activity 4COC was demonstrated to be the most potent and selective isomer 4COC is suggested to apply instead of 4CMC in experiments when the selectivity of RyR activation is critically important Abstract: In this study we performed the comprehensive pharmacological analysis of two stereoisomers of 4-chloro-meta-cresol (4CMC), a popular ryanodine receptor (RyR) agonist used in muscle research. Experiments investigating the Ca 2+ -releasing action of the isomers demonstrated that the most potent isomer was 4-chloro-orto-cresol (4COC) (EC50 = 55 ± 14 μM), although 3-chloro-para-cresol (3CPC) was more effective, as it was able to induce higher magnitude of Ca 2+ flux from isolated terminal cisterna vesicles. Nevertheless, 3CPC stimulated the hydrolytic activity of the sarcoplasmic reticulum ATP-ase (SERCA) with an EC50 of 91 ± 17 μM, while 4COC affected SERCA only in the millimolar range (IC50 = 1370 ± 88 μM). IC50 of 4CMC for SERCA pump was 167 ± 8 μM, indicating that 4CMC is not a specific RyR agonist either, as it activated RyR in a similar concentration (EC50 = 121 ± 20 μM). Our data suggest that the use of 4COC might be more beneficial than 4CMC in experiments, when Ca 2+ release should be triggered through RyRs without influencing SERCA activity.